Effects of Garlic Oil on the Migration of Neutrophil-Like Cell Studied by Using a Chemotactic Gradient Labchip. (3rd May 2010) - Shih, Po-Chen; Kuo, Chia-Hao; Juang, Jenh-Yih; Liu, Cheng-Hsien; Hsu, Long; Liu, Cheng-Tzu
Abstract : We have designed and fabricated a novel chemotactic gradient Labchip for studying cell migration quantitatively. Owing to the great potential of garlic and its preparations in developing antiinflammatory drugs, the aim of the present study is to investigate the effect of garlic oil on the locomotion of a neutrophil-like cell by measuring the dynamic features of cell migration including migration direction, average migration speed, chemotactic index (CI), and motility index (MI) with the newly designed Labchip. We found that garlic oil treatment lowered the values of CI and MI and reduced the average speed of cell migration from 13 to 8 μ m/min. The results indicate that garlic oil is a potential inhibitor for neutrophil-like cell migration and chemotactic responsiveness. By comparing with the effects of nocodazole and cytochalasin B, we also suggest that the antiinflammatory activity exhibited by garlic oil was mainly through inhibiting the assembly-disassembly processes of the cytoskeleton.